Moisture sources for the unprecedented precipitation event in the heart of Taklimakan desert - Shijie Tang; Tianjun Zhou; Lixia Zhang; Liwei Zou; Wenxia Zhang; Shijia Liu (Weather and Climate Extremes)
The Taklimakan desert, situated in western China and known for its scarcity of precipitation, experienced an unprecedented precipitation event on 13-14th May 2021. However, the moisture sources and the reason for such extreme precipitation in the heart of the desert remain unexplored. Here, leveraging rain gauge observations from Tazhong Station, situated in the heartland of the Taklimakan Desert, we employed the Flexpart Lagrangian model to examine the moisture source and transport path of this exceptional precipitation event. The target region is situated east of the 500 hPa low trough and to the right of the entrance and left of the exit area of the two upper-level jet streams, providing favorable dynamic conditions for extreme precipitation. Our analysis indicates that the water vapor transport from the eastern boundary of the target area, which originates from the westerly wind along the northern side of the Tianshan Mountains and later turns southward to the Tarim Basin, was the decisive factor for this extreme precipitation event. By employing the Flexpart model, we found that the east particles, which bypassed the Tianshan Mountains and entered the target from its eastern boundary contributed 61.7% of the precipitation, while the west particles contributed only 38.3%. Regarding overall moisture sources, southern Xinjiang emerged as the most significant contributor, accounting for 43.0% of the water vapor, followed by northern Xinjiang at 24.7%, and Central Asia at 21.2%. Our findings suggest that water vapor conditions play a more critical role than dynamic factors in driving such extreme precipitation events in the target area. The water vapor associated with the extreme precipitation event in the target area primarily originates from Southern Xinjiang and its adjacent regions. These results can help us improve the understanding of the mechanism behind extreme precipitation events in arid areas, especially in desert areas.